Widespread Adoption of Precision Anticancer Therapies After Implementation of Pathologist-Directed Comprehensive Genomic Profiling Across a Large US Health System - Dowdell, A.; Meng, R.; Vita, A.; Bapat, B.; Hanes, D.; Chang, Shu-Ching; Harold, L.; Wong, Cliff; Poon, Hoifung; Schroeder, Brock; Weerasinghe, R.; Leidner, R.; et al. (JCO Oncology Practice, 2024)
Precision therapies and immunotherapies have revolutionized cancer care, resulting in significant gains in patient survival across tumor types. Despite this transformation in care, there is variability in the utilization of tumor molecular profiling. To standardize testing, we designed a pathologist-directed test ordering system at time of diagnosis utilizing a 523-gene DNA/RNA hybrid comprehensive genomic profiling (CGP) panel. We assessed actionability rates, therapy choices, and outcomes among 3,216 patients. 49% of cases had at least one actionable genomic biomarker-driven (GBD) approved and/or guideline-recommended targeted or immunotherapy and 53% of patients would have been eligible for a precision therapy clinical trial from three large basket trials. When assessing CGP versus an insilico 50 gene panel, 67% of tumors compared to 33% harbored actionable alterations. Among patients with 6-months or more of follow-up, over 52% received a targeted therapy or immunotherapy, versus 32% that received conventional chemotherapy alone, a phenomenon not previously observed.